Catch And Length-Weight Relationship Of Freshwater Lobster, Cherax Quadricarinatus Von Martens, 1868 In Tondano Lake, Kakas District, Minahasa, North Sulawesi - Jamlean, Yosef Gerard; Bataragoa, Nego E.; Tombokan, Jhon L. (Jurnal Ilmiah PLATAX, 2018)
C. quadricarinatus (red claw) has important economic value either for consumption or as ornamental crustacean, has been  cultivated, and introduced to many waterways outside its natural habitat. In Tondano lake, C. quadricarinatus has developed and become fishing target  using traps and spearguns.  The purpose of this survey is to describe the freshwater lobster catching using traps, and to know the length-weight relationships, growth pattern and condition factor. The study was expected to use as information on the presence of C. quadricarinatus Tondano Lake. Catches were red claw, C. quadricrinatus, marble sleeper Oxyeleotris marmorata, Mud gudgeon Ophieleotris aporos, Mozambique tilapia Oreochromis mossambicus and African sharptooth catfish Clarias Gariepinus. Length-weight relationship of C. quadricarinatus was W = -1.8005 + 4.2765 log L for males, W = -1.2978 + 3.6524 log L for females, respectively, and W = -1.5631 + 3.9848 log b for combined sexes. They had positive allometric (A +) growth. Condition factor ranged from 0.60-1.43 with an average of 1.071 ± 0.17 for males and 0.46-1.36 with an average of 1.027 ± 0.18 for females, 0.59-1.642 withan average of 1.22± 0.21.Keywords: fishing, length-weight, growth pattern, fishing gear, Kakas district, MinahasaAbstrakC. quadricarinatus (red claws) mempuyai nilai ekonomis penting baik komsumsi maupun sebagai krustasea hias dan  telah banyak di budidaya serta di introduksi ke banyak perairan  di luar habitat aslinya. Di Danau Tondano, C. quadricarinatus telah berkembang biak dan menjadi target penangkapan nelayan mengunakan alat tangkap bubu dan alat tangkap tura sejenis tombak sambil menyelam. Tujuan penelitinan ini ialah untuk mendeskripsikan penangkapan lobster air tawar C. quadricarinatus menggunakan alat tangkap bubu, hubungan panjang berat, pola pertumbuhan dan faktor kondisi. Hasil penilitian ini diharapkan dapat digunakan sebagai informasi keberadaan lobster air tawar C. quadricarinatus di Danau Tondano. Hasil tangkapan yang didapat adalah lobster air tawar, ikan Betutu, ikan Payangka, ika Mujair dan ikan Lele Dumbo. Hasil hubungan panjang berat lobster air tawar di dapat jantan : W=-1,8005+4,2765 log L, betina : W=-1,2978+3,6524 log L dan gabungan ( jantan & betina) : W=-1,5631+3,9848 log L. Pola pertumbuhan ketiganya ialah allometrik positif (A+) dan faktor kondisi jantan berkisar 0,60-1,43 dengan rata-rata1,071±0,17, betina berkisar 0,46-1,36 dengan rata-rata 1,027±0,18, dan gabungan (jantan dan betina) berkisar 0,59-1,642 dengan rata-rata1,22±0,21.Kata Kunci : Penangkapan, Hubungan panjang berat, Pola pertumbuhan, Kecamatan Kakas